O filozofii formalnej Miguela Ángela Asturiasa - Szubert, Irmina (Przestrzenie Teorii, 2023)
This paper analyses the linguistic structure, creative modes of expression and stylistic properties of Miguel Ángel Asturias’s Legends of Guatemala (Leyendas de Guatemala, 1930). Furthermore, it attempts to classify Asturias’s prose fiction, which is often multifaceted, by defining the unique character of its complex linguistic mechanisms that create his debut short-story collection. All texts in Legends contain references not only to events of the Mayan cosmogony, mythological tropes and motifs (that have been developed and put into a new context), but also to their mimetic relationship with the ritual language used in the Popol Vuh. The word order variations and certain combinations of vowels and consonants, as well as the specific syntactic parallelisms and enumerations (stylistic and lexical “props”) imitate formulaic phrases which are important elements in oral style. Pre-Columbian themes – especially those chosen by the Guatemalan writer for the narrative content of his works – are full of visual symbols with rich folk meanings; the melodic sound of Asturias’s narration (and its internal rhythm) seems attuned to the worldview belonging to both particular and universal human communities.